The Role of Cooperative Learning Strategies in Enhancing Speaking Skills and Learner Autonomy - Jumaboyeva, Sevara Anvar qizi; Karimov, Ulugʻbek Nusratovich (The Lingua Spectrum, 2026)
Speaking is considered one of the most important skills in learning English as a foreign language; however, many students face difficulties in communicating effectively. Learners often struggle with fluency, lack confidence while speaking, and find it challenging to express their ideas clearly. This article investigates how cooperative learning strategies can support the development of speaking skills while also promoting learner autonomy in English language classrooms. Cooperative learning creates an environment where students actively interact with one another, exchange opinions, and support each other during the learning process. Activities such as think-pair-share, role plays, group discussions, and jigsaw tasks provide learners with more opportunities to use English in meaningful and realistic situations. Through these collaborative activities, students gradually become more confident speakers, improve their vocabulary and fluency, and develop stronger communication skills in a less stressful and more supportive atmosphere. Based on classroom observations and findings from previous studies, this article highlights that cooperative learning not only improves students’ speaking ability but also encourages them to become more independent and responsible learners. By participating actively in group tasks and taking greater responsibility for their own learning, students develop autonomy, motivation, and confidence, which are essential for successful language learning and effective real-life communication.